The demographics of talipes equinovarus in Indiana, with a particular emphasis on comparisons between clubfoot types. Issue 1 (January 2023) - Akinyoola, Lawrence A.; Gunderson, Zachary J.; Sun, Seungyup; Fitzgerald, Ryan; Caltoum, Christine B.; Christman, Tyler; Bielski, Robert; Loder, Randall T.
Abstract : Talipes equinovarus (TEV) can be an isolated idiopathic deformity or associated with various syndromes. The purpose of our study was to examine the demographics of TEV in Indiana. All TEV patients from 2010 to 2019 from our institution were reviewed, recording standard demographic variables. The socioeconomic level of the family was determined using the 2018 Area Deprivation Index (ADI). There were 568 patients; 456 had idiopathic TEV and 112 syndromic. Within the idiopathic group, 69.1% were male, 92.1% were typical and 7.9% were atypical. Medical issues during the pregnancy occurred in 19.5%, maternal smoking in 2.9%, hypertension in 3.9% and diabetes in 5.3%. The most common syndromic patients were myelomeningocele (29%) and arthrogryposis (17%). Patients with syndromic TEV had more bilateral involvement (68.2% vs. 45.2%) and other associated congenital deformities (67.0% vs. 11.4%). TEV was less common in Hispanics and Asians but more common in Whites and Blacks ( P = 0.003). Complex TEVs were less frequent in White (6.9%) and Black (5.0%) and more common in Hispanic (30%) children ( P = 0.0002). The ADI demonstrated no difference in prevalence across socioeconomic levels. There were no differences by state ADI levels for TEV type (syndromic/idiopathic), sex, maternal smoking or illicit drug use, or typical/complex TEV. This study is the first to describe the demographics of TEV in Indiana, demographic differences between typical and complex types of clubfeet, and TEV patients using the ADI. TEV did not show any difference in prevalence by socioeconomic level.